Mediasi Profitabilitas Terhadap Hubungan Antara Ukuran Perusahaan Dengan Struktur Modal - Ana Susi Mulyani (Tirtayasa Ekonomika, 2023)
The Purpose of this Study was to determine the role of Profitability as a mediating variable in the relationship between Firm Size and Capitas Structure, as wel as determine the effect of Firm Size on Capital Structure. The type of research is quantitative research, the sampling method used is  non-probability sampling method with a total sample of 11 automotive and component sub- sector companies listed on the Indonesia Stock Exchange for the period 2016 – 2020. The analytical method used in this study is descriptive statistics and path analysis..The results indicate Size prove that have not negative effect on Capital Structure, Size prove that have positive significant effect on Profitability, Profitability prove that have negative not significant effect to Capital Structure, and Profitability Can’t Mediate Size to Capital Structure.